Proposing New Routing Protocol Based on Chaos Algorithm - Majdi, Ali (Review of Computer Engineering Research, 2022)
In MANET, the multicast routing is considered a non-deterministic polynomial (NP) complexity, it contains assorted objectives and restrictions. In the multicast issue of MANET, the quality of services (QoS) based upon cost, delay, jitter, bandwidth, are constantly deemed as multi-objective for directing multicast routing protocols (MR). Conversely, a mobile node has finite battery energy and the lifetime of a network depends on its mobile node battery energy. Here, the MR problem of MANET has five objectives vis-a-vis the optimization of cost, delay, jitter, bandwidth, and network lifetime with the help of Chaotic-CSA-ROA. Here, evaluation metrics, via delay, delivery ratio, drop, Network lifespan, overhead and throughput are analyzed with node, rate, and speed. The proposed QOS-MRP-CSROA-MANET provides higher throughput at the node between 32.9496% and 65.5839%, and higher throughput in rate as 16.6049% and 30.4654%, higher throughput in speed as 10.1298% and 7.0825%, low packet drop in node as 63.7313% and 52.2255%, low packet drop in rate as 51.5528% and 25.6220%, low packet drop in speed as 18.0857% and 24.5953% compared with existing methods, like QoS aware of multicast routing protocol using particle swarm optimization algorithm in MANET (QOS-MRP-PSOA-MANET) and QoS aware of multicast routing protocol using a genetic algorithm in MANET (QOS-MRP-GA-MANET) respectively.